2000
DOI: 10.1074/jbc.275.3.1976
|View full text |Cite
|
Sign up to set email alerts
|

Transport and Pharmacological Properties of Nine Different Human Na,K-ATPase Isozymes

Abstract: Na,K-ATPase plays a crucial role in cellular ion homeostasis and is the pharmacological receptor for digitalis in man. Nine different human Na,K-ATPase isozymes, composed of 3 ␣ and ␤ isoforms, were expressed in Xenopus oocytes and were analyzed for their transport and pharmacological properties. According to ouabain binding and K ؉ -activated pump current measurements, all human isozymes are functional but differ in their turnover rates depending on the ␣ isoform. On the other hand, variations in external K ؉… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
378
3
15

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 395 publications
(432 citation statements)
references
References 46 publications
27
378
3
15
Order By: Relevance
“…The selective expression of NKAα3 provides unique insight into the physiological demands on the myelinated fibers in the cochlea. The NKAα3 is distinguished from the NKAα1 by its relatively low affinity for intracellular sodium (Jewell and Lingrel 1991;Munzer et al 1994;Zahler et al 1997;Crambert et al 2000), high affinity for ATP (Jewell and Lingrel 1991), and lack of inhibition at hyperpolarized potentials (Balshaw et al 2000;Crambert et al 2000). Thus, NKAα3 may be especially suited for the myelinated fiber types of the cochlea that sustain high rates of activity that would be expected to raise intracellular sodium concentrations, deplete ATP, and maintain hyperpolarized membrane potentials.…”
Section: Discussionmentioning
confidence: 99%
“…The selective expression of NKAα3 provides unique insight into the physiological demands on the myelinated fibers in the cochlea. The NKAα3 is distinguished from the NKAα1 by its relatively low affinity for intracellular sodium (Jewell and Lingrel 1991;Munzer et al 1994;Zahler et al 1997;Crambert et al 2000), high affinity for ATP (Jewell and Lingrel 1991), and lack of inhibition at hyperpolarized potentials (Balshaw et al 2000;Crambert et al 2000). Thus, NKAα3 may be especially suited for the myelinated fiber types of the cochlea that sustain high rates of activity that would be expected to raise intracellular sodium concentrations, deplete ATP, and maintain hyperpolarized membrane potentials.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, an increase in α3 expression may result in facilitation of excitation spread across the gap junction in hypertrophied cardiac myocytes. The expression of α and β subunits in oocytes revealed that the α3β2 isozyme had a higher affinity for Na + ion than did the α3β1 and α3β3 isozymes [3]. This property of the α3β2 isozyme may help in removing Na + ions efficiently from the cytoplasm in the intercalated disc, and as a result H + ions may turn out to be efficiently effluxed.…”
Section: Functions Of Na + K + -Atpase Isozymesmentioning
confidence: 98%
“…There are four α and three β isoforms, and the expression of the α and β subunits have been reported to be developmentally regulated in a cell-specific manner [2]. Although the expression of α and β subunits in oocytes [3] or Sf-9 cells [1], an insect cell line, revealed every combination of α and β subunits was functional, Na + ,K + -ATPases in cells in situ are thought to exist as a specific combination of α and β subunits [4,5]. Furthermore, single cells have been shown to have multiple α subunits, which are distributed differently in the cell membrane [6].…”
mentioning
confidence: 99%
“…Why are so many Na/K-ATPase isoforms required? The most logical view on their diversity is that differences in cation and ATP affinity of each isozyme are essential for adapting Na/K-ATPase activity to specific physiological conditions (157). Isozymes of Na/K-ATPase, composed of different combinations of alpha and beta subunit isoforms, have unique properties and are subject to developmental and hormonal regulation (158)(159)(160)(161)(162)(163)(164)(165)(166)(167)(168)(169)(170)(171)(172)(173)(174)(175).…”
Section: Na/k-atpase and Blastocyst Formationmentioning
confidence: 99%